Analisis Unsur Intrinsik Roman “Emil und die Detektive” Karya Erich Kästner - Devi Eka Purba; Mantasiah Mantasiah (Universitas Negeri Makassar, 2023)
Abstract. This study aims to describe the intrinsic elements in the form of characters, setting, plot, point of view, theme, and moral value in the novel